From Victims to Beneficiaries: Shaping Postconflict Subjects through State Reparations in Peru. (September 2019) - Ramírez Zapata, Ivan; Scott-Insúa, Rogelio
The political and institutional coordinates that appear in official classifications of the victims of the Peruvian armed conflict (1980–2000) affect their subsequent recognition as beneficiaries of reparations programs. A review of the conceptual bases of the Comprehensive Reparations Program calls attention to the tension in the design and implementation of this program between a strictly reparative approach and another that addresses the structural disparities present in the aftermath of the war. Examination of the effects of that tension in two cases shows that the early stages of implementing housing reparations equated the concept of "victim" with that of "poor" and later made poverty a prerequisite for receiving housing reparations and points to the difficulty of making an appropriate offer of reparations for displaced persons, whose specific problems are not properly addressed by the traditional agenda of transitional justice. Las coordenadas políticas e institucionales que atraviesan la calificación oficial de las víctimas del conflicto armado peruano (1980–2000) afectan su consiguiente reco-nocimiento como beneficiarios de programas de reparación. Al revisar los fundamentos conceptuales del Programa Integral de Reparaciones destacamos una tensión tensión en el diseño e implementación de este programa entre una perspectiva propiamente de reparación y una perspectiva de combate a las disparidades estructurales presentes en el período posconflicto. Examinamos la presencia y efectos de esta tensión en dos casos concretos. El primero muestra cómo los inicios en la implementación de reparaciones en vivienda equipararon la figura de la víctima con la de pobre, y posteriormente pusieron a la pobreza como requisito para recibir reparaciones en vivienda. El segundo muestra la dificultad de proponer una oferta adecuada de reparaciones para personas desplazadas, al ser una población cuyas características no encajan en la agenda clásica de la justicia transicional.